Characterisation of auxin and auxin-related genes in the response of Arabidopsis thaliana to salt stress - Cackett, Lee (Department of Molecular and Cell Biology, 2020)
Soil salinization is prominent in agricultural land and has detrimental effects on plant growth and yield. Salt imposes both an osmotic and ionic stress on plants, and the aim of this study was to investigate the molecular basis of the plant response to the ionic component of salinity stress. To do so, transcriptome profiling using microarrays was performed at two developmental stages (two and four weeks post-germination) exposing plants to either NaCl (which imposes an osmotic and ionic stress) or iso-osmolar sorbitol (which imposes osmotic stress only). Clear transcriptomic differences in the plant response to NaCl and sorbitol were observed, allowing the identification of genes that may be involved specifically in the response to the ionic component of salinity stress. Differences in salt-responsive gene expression were also observed between early and later development as well as root and shoot tissues, indicating that there may be both developmental and tissue specific responses to NaCl. ‘Response to auxin’ was a highly enriched gene ontology term associated with genes that are significantly induced specifically in response to ionic stress, suggesting a potential role for this plant growth hormone in ionic stress tolerance. This hypothesis was supported by mass spectrometry analysis which demonstrated that active IAA levels show a significantly greater increase in response to NaCl than to sorbitol, demonstrating an ionic specific auxin response. In planta quantification and spatial distribution of IAA was further analysed in salt stressed plants using two auxin reporter lines, DR5::GUS and DII::VENUS. These analyses showed that IAA levels increased in the shoot and root tip in response to NaCl. Also, local IAA maxima distributed along the primary root of salt stressed seedlings were decreased compared to the untreated control, which may explain the decrease in lateral root number and primary root bending observed in salt stressed plants. There are several different pathways in the tryptophandependent auxin biosynthesis process, each with unique biosynthetic intermediates and ratelimiting enzymes. For this reason, changes in the levels of the different IAA biosynthetic intermediates were analysed in NaCl and sorbitol stressed Arabidopsis to identify a predominant pathway responsible for increasing IAA during ionic stress. The changes in IAN (the IAA biosynthetic intermediate of the IAOx pathway) in response to NaCl and sorbitol mirrored those observed for IAA. Additionally, mRNA levels of Nitrilase 2 (which converts IAN to IAA) were significantly increased in response to NaCl but not sorbitol. Taken together, these results suggest that IAA biosynthesis is increased in response to NaCl via the hydrolysis of IAN to IAA by NIT2. In agreement with this, a Nit2 overexpressing line (35s::Nit2) displayed both improved survival and growth in the presence of NaCl. Furthermore, the Nit2 overexpressor had increased IAA but deceased IAN compared to wild type plants in response to salt stress. Together these results indicate that Nit2 is likely involved in the salt stress response through altering IAA levels in planta. GH3.12 and ILL6, two genes involved in IAA storage and/or degradation via hydrolysis and conjugation to amino acids, were also differentially expressed in response to NaCl at both developmental stages tested. However, mutants for ill6 and gh3.12 were not altered in their salt tolerance, suggesting that IAA storage and/or degradation may not play an important role in modulating active IAA levels in response to salt stress. Finally, preliminary evidence was obtained that the expression of sorghum Nit2 homologs is also increased in response to salt stress, implying that auxin might play a role in salt tolerance across a phylogenetically broad range of plants, making this a potential route to improve salt tolerance in crop plants. Overall, this study provides novel information indicating that IAA levels are altered specifically in response to the ionic component of salinity stress which may contribute to the altered plant growth observed under these conditions, as well as the identification of an auxin-related candidate gene which can improve salt tolerance in plants when overexpressed.